Serrated flow accompanied with dynamic type transition of the Portevin–Le Chatelier effect in austenitic stainless steel. (10th January 2023) - Lee, Seung-Yong; Chettri, Sita; Sarmah, Ritupan; Takushima, Chikako; Hamada, Jun-ichi; Nakada, Nobuo
Highlights: By introducing high-temperature DIC analysis, the PLC effect in an austenitic stainless steel was investigated. Serration type dynamically changed even at an applied strain rate at temperatures from 473 to 623 K. The dynamic type transition of serrated flow obeyed the variation in PLC band nucleation and propagation behavior. The spatial-temporal coupling effect plays an important role in the microscopic nucleation manner of the PLC band. Abstract: In order to further understand high-temperature deformation behavior and its-related mechanical properties, the Portevin–Le Chatelier (PLC) effect in an Fe–19Cr–13Ni–0.2C austenitic stainless steel was investigated using high-temperature digital image correlation (DIC) analysis. Under the tensile testing at temperatures from 473 to 623 K, different types of serrated flow appeared even at a constant applied strain rate, and the type transition took place dynamically in a certain order with deformation time. DIC analysis revealed that the dynamic type transition of the serrated flow obeys the PLC band propagation behavior, and that the transition of the PLC band propagation behavior could be attributed to the PLC band nucleation manner. Numerical modeling also proved that the nucleation manner of PLC band nucleation is determined by the spatial-temporal coupling effect.